Exploring Natural Bioactive Compounds for Radiation Countermeasure Properties: A Review - Lyngdoh, Toijam Sanjeev; Ningombam, Dollyca; Yumnamcha, Thangal; Devi, Maibam Damayanti (International Journal of Pharmaceutical Investigation, 2026)
Radiation-induced toxicity poses significant challenges in radiation therapy, nuclear incidents, industrial, and other occupational applications. This review investigates the potentiality of natural bioactive compounds as defences against such toxicity. The study objectives include a comprehensive literature review, evaluation of compound efficacy, clarification of mechanisms, translational potential assessment, and identification of future research directions. Using a systematic methodology, peer-reviewed studies were carefully gathered from institutional library and databases including PubMed, ResearchGate, and Google Scholar. Qualitative analysis revealed patterns and trends in compound effectiveness. The review highlighted natural bioactive compounds like polyphenols, flavonoids, phenolic acids, ginseng, curcumin, and garlic among others, which exhibit antioxidant, anti-inflammatory, and DNA-protective effects. These compounds show promise in alleviating radiation-induced damage across different bodily tissues. Given the substantial health risks linked to ionizing radiation exposure, effective health-protective strategies are imperative to counter radiation-induced toxicities. Advancements in understanding signaling pathways and developing innovative radiation countermeasure agents offer avenues for better management of radiation toxicity. Future research directions involve robust clinical trials, clarification of molecular mechanisms, exploration of synergistic interactions, and long-term assessments of efficacy and safety.
Keywords: Bioactive compounds; Health-protective strategies; Ionizing radiation; Radiation countermeasure.